Evaluation of artificial field infestation techniques with Striga Hermonthica for resistance screening in maize (Zea mays L.) - Ibikunle, O.A.; Menkir, A.; Kamara, A.Y.; Ajeigbe, Hakeem A.; Smith, M.A. (2008)
Breeding for resistance to Striga can be done effectively under high and uniform artificial field infestation. To identify Striga tolerantresistant maize genotypes, it is essential to artificially inoculate every hill of maize in the breeding nursery with Striga seeds. The present method of inoculation is expensive, time-consuming and labour-intensive. Two inoculation methods, covering the Striga seed with or without a layer of sand, were compared using two Striga susceptible, TZB-SR and 8338-1 and two Striga tolerantresistant genotypes, Acr.97 TZL COMP.1-W and 9022-13 STR. The two methods of inoculation had no significant effects (P<0.05) on Striga emergence, host plant damage scores and grain yield. The genotypes exhibited significant differences (P<0.001) for Striga emergence counts, host plant damage scores and grain yield. Inoculating Striga seeds in the field without a layer of sand required less labour. These results suggest that the revised method that does not require covering with a layer of sand can be used for screening a large number of breeding lines for resistance to Striga within a short period of time.